The struggle for individuality: Investigating a long-term pursuit of a lifestyle sport activity - Jana Hoffmannová; Luděk Šebek; Pete Allison; Michael Maina; James Toogood (Palacký University Olomouc, 2016)
Background: Mainstream forms of media frequently portray "wild" or "epic" images of lifestyle sport activities showing the participants as "modern-day gladiators". This research set out to explore how closely aligned these stereotypes are with individual experiences. Objective: The purpose of this study was to identify and analyze factors which may contribute to a selected lifestyle sport activity becoming firmly rooted in an individual's life course. Methods: Data were collected through focus groups, individual interviews, lifeline method, and participant observation within focus groups. The sample included performance freeskiers, freestyle snowboard riders and instructors (N = 19). Grounded theory was used for analysis and interpretation of data. Results: Results from this research indicate traditional deterministic images of a sport career in freeskiing and freestyle snowboarding do not match the views and beliefs of the actual participants in these activities. Conclusions: The study examines the careers of long-term participants in freeskiing and freestyle snowboarding and extends existing knowledge of lifestyle sports through the implementation of the lifespan approach. Recommendations for future research include extending the analysis to include sports recently considered mainstream as the distinction (between mainstream and lifestyle sports) is becoming increasingly complicated.